Intra-Household Work Timing: The Effect on Joint Activities and the Demand for Child Care - Chris van Klaveren; Henriette Maassen van den Brink; Bernard M.S. van Praag (Tinbergen Institute, 2011)
This study examines if couples time their work hours and how this work timing influences child care demand and the time that spouses jointly spend on leisure, household chores and child care. By using a innovative matching strategy, this studies identifies the timing of work hours that cannot be explained by factors other than the partners' potential to communicate on the timing of their work.The main findings are that couples with children create less overlap in their work times and this effectis more pronounced the younger the children. We find evidence for a togetherness preference of spouses,but only for childless couples. Work timing also inuences the joint time that is spent on householdchores, but the effect is small. Finally, work timing behavior affects the demand for informal child care,but not the demand for formal child care.
Keywords: D13; I31; J12; J22; 330; Labor supply; Work timing; Time allocation; Familienökonomik; Arbeitszeit; Freizeit; Kinderbetreuung; Nachfrage; Schätzung; Niederlande